Effect of Low-Cost CPR Pillow Training on Adolescents’ Willingness to Perform Bystander CPR: A Quasi-Experimental Study - Lukman, Lukman; Wijaya, Sapondra; Susmini, Susmini; Wibowo, Wahyu Dwi Ari; Ningsih, Nurna; Soewito, Bambang (Journal of Applied Nursing and Health, 2026)
Background: Despite increasing CPR education initiatives, evidence regarding the effectiveness of low-cost CPR Pillow simulation in improving adolescents' willingness to perform bystander CPR remains limited. This study aimed to evaluate the effect of CPR Pillow training on scout members' willingness to perform CPR in Lubuklinggau City, South Sumatera, Indonesia. Methods: This quantitative quasi-experimental study followed a non-equivalent control group pretest-posttest design in line with TREND principles. Seventy-two scout members aged 15–17 years who had never received CPR training were selected by random sampling and allocated to intervention and control groups. The intervention group received three sessions of classical teaching combined with CPR Pillow simulation over two months, while the control group received classical CPR training using leaflets only. Willingness to perform CPR was measured using a 30-item questionnaire with Cronbach's alpha of 0.85 and analyzed using paired and independent t-tests. Results: The intervention group demonstrated a greater increase in willingness scores than the control group, with mean scores improving from 42.50 ± 7.00 to 86.90 ± 5.60. The control group also improved, from 42.30 ± 6.90 to 84.20 ± 5.90. The between-group difference in score change was statistically significant (t = 2.398, p < 0.001). Conclusion: Low-cost CPR Pillow training significantly improved adolescents’ willingness to perform bystander CPR compared with leaflet-based training. This approach may be a practical and scalable strategy for school and scout CPR education in low-resource settings.